Lipid lowering effect of Eurycoma longifolia Jack aqueous root extract in hepatocytes. - Lim, Pei-Jean; Gan, Chye-Sheng; Yusof, Ashril (Kuwait Journal of Science, 2019)
An aqueous extract of Eurycoma longifolia Jack, or natively known in Malay as Tongkat Ali, roots is traditionally used to overcome plethora of health conditions especially andrological maladies. As compiling evidences corroborate the therapeutic effects of this plant extract as efficacious concoction, it is noteworthy that novel potential for the use of the plant extract in regulating fat metabolism is being unravelled. Due to studies that investigated the effects of Tongkat Ali on in vivo models and clinical subjects where the measurable parameters were the end stage of response, this study adopts an in vitro model to investigate whether Tongkat Ali root extract possesses lipid lowering potential or the changes was a side-effect of the supplementation. Human hepatic cell line WRL-68 was used in this study and treated with various concentrations (1, 2, 4 and 8 µg/ml) of the aqueous Tongkat Ali root extract were conducted on fatty liver cells. Results demonstrated reduced intracellular fatty acids build up, up to 72% reduction, in treated cells when compared to those untreated control cells. This study therefore, unravelled the novel potential of intracellular lipid lowering effect of Tongkat Ali. The finding therefore, warrants further studies to elucidate the mechanisms that explain the phenomenon.